Female Employee Engagement as a Mediator of the Influence of Leadership, Empowerment, and Organizational Climate on Employee Performance in the Narcotics Enforcement Unit of Customs and Excise - Toumahuw, Novi Yohanes; Rekarti, Endi; Meliala, Janita S (Dinasti International Journal of Education Management and Social Science, 2025)
This study stems from the growing importance of female employees in the Narcotics Enforcement Unit of the Directorate General of Customs and Excise (DGCE), particularly as drug-related offenses involving women continue to rise. In this context, leadership, employee empowerment, and organizational climate are considered key factors that may shape employee engagement and, ultimately, job performance. The purpose of this research is to examine how these organizational factors influence the engagement and performance of female employees working in narcotics enforcement units within DGCE. A quantitative research design was employed using Structural Equation Modeling. The measurement model was validated through Confirmatory Factor Analysis, and hypothesis testing was conducted using PLS-SEM. Data were collected from 211 female employees through a structured questionnaire, and all research instruments were tested for reliability and validity prior to data analysis. The findings reveal that leadership and organizational climate significantly affect employee performance through the mediating role of engagement. In contrast, employee empowerment does not show a significant effect on performance when mediated by engagement. These results are supported by measurement indicators that demonstrated strong validity and reliability. The study highlights the importance of strengthening leadership quality and fostering a supportive organizational climate to enhance engagement and improve the performance of female employees in narcotics enforcement. These insights may guide DGCE management in developing human resource strategies that are more responsive to the unique needs and contributions of women in high-risk enforcement environments.